Can the systemic inflammation score be used to predict prognosis in gastric cancer patients undergoing surgery? A systematic review and meta-analysis - Liu, Shuai; Yu, Xiaowei; Ye, Feifei; Jiang, Liangxian (Frontiers in Surgery, 2022)
Background: Inflammatory markers are being increasingly used to predict the prognosis of cancer patients. We hereby conducted the first meta-analysis assessing the association between systemic inflammation score (SIS) and prognosis of gastric cancer patients undergoing surgical intervention. Methods: A literature search was carried out on PubMed, CENTRAL, Scopus, and Embase up to 3rd June 2022 for relevant studies. Adjusted data reported as hazard ratios (HR) was combined in a random-effects model. Results: A total of seven studies with 5338 patients could be included. All studies were from either China or Japan and published in the last four years. Meta-analysis showed that higher SIS scores (1 or 2) were significant predictors of poor overall survival (OS) in gastric cancer patients (HR:1.25 95% CI: 1.05, 1.49 I2=11%). Similarly, the meta-analysis demonstrated that an SIS score of 2 was associated with poor OS as compared to scores of 0/1 (HR:2.53 95% CI: 1.30, 4.89 I2=45%). Data on disease-free survival (DFS) was scarce to draw conclusions. Conclusion: The SIS score can be a simple and useful tool to predict OS in gastric cancer patients undergoing surgery. Data on DFS is scarce and conflicting. Future studies should report using standard reference groups and provide data on DFS to enhance current evidence.